ANCA-associated Glomerulonephritis - Tansakul, Eakchakarj; Srisuwarn, Praopilad (Journal of the Nephrology Society of Thailand, 2023)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis is a group of systemic diseases that involves small blood vessels of multiple organ systems. ANCA-associated vasculitis is classified into three subtypes: granulomatosis with polyangiitis, eosinophilic granulomatosis with polyangiitis, and microscopic polyangiitis. The kidney involvement known as ANCA-associated glomerulonephritis which represents severe manifestation of ANCA-associated vasculitis is more commonly observed with eosinophilic granulomatosis with polyangiitis and microscopic polyangiitis. The underlying mechanisms involve the attack of antibodies on the neutrophils which in turn activates immunologic and complement systems resulting in injuries of small blood vessels. To make a diagnosis, serologic tests for antibodies are particularly helpful because of the convenience and the high diagnostic yield. Nevertheless, the kidney biopsy remains a gold standard for diagnosis and is necessary prior to treatment with immunosuppression. For the past decades, cyclophosphamide has been the cornerstone for induction therapy in combination with plasma exchange in severe cases. Recently, rituximab has shown comparable efficacy with cyclophosphamide with less toxicities. Avacopan has demonstrated non-inferior efficacy to glucocorticoid with less metabolic side effects. Novel insights into the pathogenesis is crucial in finding new therapeutic targets that will help improve outcomes and prognosis of patients with ANCA-associated vasculitis.